Behavior of Nitrogen Use Efficiency in Maize (Zea mays L.) Under Different Management Conditions in Veracruz, Mexico (Agro Productividad, 2025)
Currently, technological packages primarily aim to achieve high economic performance without considering environmental impact. This approach promotes the use of agrochemicals, leading to high production costs and negative environmental consequences, while disregarding the efficiency of agro-productive systems.The objective of this research was to determine dry matter production, nitrogen (N) absorption, and nitrogen use efficiency (NUE) under different maize (Zea mays L.) management conditions. The experiment was conducted at the Colegio de Postgraduados, Campus Veracruz.Using 300-gauge black polyethylene bags, 16 treatments were evaluated, resulting from the combination of the following factors: soil type (crumbly-sandy and loamy), genotype (the hybrid "Orca®" seed from Monsanto and the native variety "Olotillo"), nitrogen application (0 and 140 kg N ha⁻¹), and the presence or absence of agricultural lime. A Taguchi L8 orthogonal array was used in a randomized block design with four replications.For the variables leaf dry weight and root dry weight, significant statistical differences were observed in favor of nitrogen application. The percentage of nitrogen absorption by the plant showed no significant differences for any of the factors or their interactions, whereas nitrogen absorption in grams was higher in fertilized plants. Finally, nitrogen use efficiency (NUE) was higher in unfertilized plants, and the interaction between soil texture and nitrogen concentration was significant.